Animal Feed Science and Nutrition Production, Health and Environment - Kumar Patra, Amlan (Veterinary Medicine and Science, 2022)
Animal food production faces many challenges including shortage of high-quality feed ingredients, contribution of greenhouse gases and pollutants to the environment, development of antimicrobial resistance, food safety, and animal health and welfare. This examines these issues over three sections. The first section is the introduction. The second section provides insights into optimization of pasture utilization employing different supplements and feed additives to maximize beef cattle production, use of insect meal as a promising protein feed ingredient, and ruminal microbiome manipulation to improve ruminal fermentation efficiency. The third section discusses accurate estimation of enteric methane emission factors, reduction of enteric methane emissions by means of feeding management and antimethanogenic compounds, and different heavy metal pollution by poultry wastes and associated health hazards.